Layered multifunctional antibacterial hydrogel dressing as well as preparation method and application thereof

By adopting a multifunctional antibacterial hydrogel dressing with a layered structure in the wound dressing, the antibacterial and photothermal effects of copper-based nanoneedles and titanium nitride nanopowder are used, and the antibacterial and photothermal effects of hyaluronic acid hydrogels are combined with the water absorption and water retention ability of hyaluronic acid hydrogels are solved, and the healing difficulties of infectious wounds are achieved, achieving rapid hemostasis, antibacterial and healing effects are achieved.

CN119701076AActive Publication Date: 2025-03-28XI AN JIAOTONG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411941107.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The prior art has problems of antibacterial resistance, wound hypoxia and difficulty in promoting healing when treating infectious wounds.

Method used

The layered multifunctional antibacterial hydrogel dressing is used, and the functions of unidirectional water pumping, antibacterial, hemostasis and oxygen supply are achieved by adding copper-based nanoneedles and titanium nitride nanopowder to the chitosan layer, and combining the hyaluronic acid hydrogel layer.

Benefits of technology

Significantly promote the healing of infectious wounds, improve the concentration of coagulation factors and hemostasis effect at the wound, solve the problem of wound hypoxia, enhance antibacterial performance, and improve the wound healing speed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701076A_ABST
    Figure CN119701076A_ABST
Patent Text Reader

Abstract

The invention discloses a layered multifunctional antibacterial hydrogel dressing as well as a preparation method and application thereof. CuO2 is formed on the surface of needle-like nano Cu (OH) 2 by adopting an in-situ oxidation method to obtain a copper-based nano needle; uniformly dispersing titanium nitride nano powder in an acetic acid solution of chitosan, soaking in an ethanol suspension of a copper-based nanoneedle, and performing vacuum drying to obtain a chitosan layer; the preparation method comprises the following steps: uniformly mixing an aldehyde polyaspartic acid aqueous solution and a hydrazide hyaluronic acid aqueous solution, standing to form a hyaluronic acid hydrogel layer, placing a chitosan layer on the hyaluronic acid hydrogel layer, and freeze-drying to obtain the layered multifunctional hydrogel dressing. The layered hydrogel dressing organically integrates the functions of seepage removal, oxygen supply, antibiosis, hemostasis, angiogenesis promotion and the like of a one-way pump, an innovative design scheme is provided for the multifunctional antibacterial dressing, and the layered hydrogel dressing has good application prospects in wound hemostasis and infectious wound treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomaterials, and in particular to a layered multifunctional antibacterial hydrogel dressing and a preparation method and application thereof. Background Art

[0002] Exudate and bleeding are common phenomena in skin wounds, especially large open wounds and burn wounds, but they can easily lead to infection. At present, the main materials for exudate absorption and hemostasis are traditional dressings such as gauze and bandages, which have the advantages of low price, wide source, and easy production. They play an important role in protecting wounds and draining exudate. However, traditional dressings can neither promote wound healing nor treat wound infection. At the same time, it is difficult to maintain the moist environment of the wound, resulting in adhesion between the dressing and the wound, causing secondary damage to the wound, which brings pain to the patient.

[0003] Hydrogel dressings are polymer hydrogel dressings that can hold dozens of times their own weight. They have unique properties such as extracellular matrix-like properties and structure, exudate absorption, and maintaining a moist wound microenvironment. They can not only serve as a barrier to protect the wound surface and resist external infection, but also facilitate oxygen penetration, promote cell migration and tissue regeneration, and accelerate wound healing. In addition, hydrogels can also carry antibacterial and healing-promoting drugs. At present, hydrogel dressings have become the most attractive type of wound dressings.

[0004] Wound exudate not only affects the speed of wound healing, but also easily irritates the skin around the wound, causing eczema and even bacterial infection. Bacterial infection, in particular, can seriously affect the speed of wound healing. In order to give hydrogel dressings antibacterial properties, antibiotics and other antibacterial drugs are usually added to hydrogels, but there are still problems such as antibacterial resistance or side effects caused by long-term use. On the other hand, maintaining a certain level of oxygen concentration in the wound plays an important role in ensuring normal cell growth and promoting tissue regeneration. Therefore, the development of hydrogels with multiple functions such as rapid hemostasis, rapid absorption of wound exudate, antibacterial, oxygen supply, and promotion of healing is expected to solve the problem of difficult healing of complex infected wounds. Summary of the invention

[0005] In order to overcome the problems of antimicrobial drug resistance, relieve wound hypoxia and promote the healing of chronic wounds, the purpose of the present invention is to provide a layered multifunctional antibacterial hydrogel dressing and its preparation method and application, which has the advantages of excellent biocompatibility, antibacterial properties, one-way water pumping performance, hemostasis, etc., and can significantly promote the healing of infectious wounds. Among them, the chitosan layer quickly transfers the wound exudate to the hyaluronic acid hydrogel layer through capillary action, which is beneficial to increase the concentration of coagulation factors at the wound and quickly stop bleeding; chitosan, titanium nitride photothermal effect and copper ions and their Fenton-like catalytic properties show excellent antibacterial properties; copper-based nanoneedles can continuously release oxygen and copper ions, which can solve wound hypoxia, promote cell migration and angiogenesis, and thus accelerate wound healing.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a layered multifunctional antibacterial hydrogel dressing comprises the following steps:

[0008] The in-situ oxidation method was used to form CuO2 on the surface of needle-shaped nano-Cu(OH)2 to obtain copper-based nano-needles.

[0009] The titanium nitride nanopowder is uniformly dispersed in an acetic acid solution of chitosan, freeze-dried, and then soaked in an ethanol suspension of copper-based nanoneedles and vacuum-dried to obtain a chitosan layer;

[0010] The aldehyde-modified polyaspartic acid aqueous solution and the hydrazide-modified hyaluronic acid aqueous solution are mixed evenly, and allowed to stand to form a hyaluronic acid hydrogel layer. A chitosan layer is placed on the hyaluronic acid hydrogel layer, and freeze-dried to obtain a layered multifunctional hydrogel dressing.

[0011] Furthermore, the length of the copper-based nanoneedle is 50-600 nm and the diameter is 5-10 nm.

[0012] Further, the preparation steps of the copper-based nanoneedles are:

[0013] The copper salt aqueous solution is mixed with the dispersant aqueous solution, and then the NaOH solution is added and stirred to form needle-shaped nano Cu(OH)2, and then the H2O2 solution is added to react to obtain copper-based nano needles.

[0014] Furthermore, the copper salt is CuCl2 or Cu(NO3)2, and the dispersant is polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide or polyvinyl alcohol.

[0015] Furthermore, the concentration of the copper salt aqueous solution is 10-100 mmol / L, the mass concentration of the dispersant aqueous solution is 0.1%-10%, the volume ratio of the copper salt aqueous solution to the dispersant aqueous solution is 1:1-10:1, the molar ratio of the copper salt to NaOH is 1:50-1:4, the concentration of the H2O2 solution is 0.1-1 mol / L, and the molar ratio of the copper salt to the H2O2 solution is 1:50-1:2.

[0016] Further, the chitosan layer is prepared by the following steps:

[0017] Chitosan is dissolved in an acid solution, and then titanium nitride powder is added, and after being evenly dispersed by ultrasonication and freeze-dried, the solution is immersed in a copper-based nanoneedle ethanol suspension, and vacuum dried to obtain a chitosan layer.

[0018] Furthermore, the particle size of the titanium nitride powder is 10 to 300 nm, the deacetylation degree of chitosan is ≥95%, and the viscosity is 100 to 200 mPa·s; the mass ratio of chitosan to acetic acid is 2:1 to 50:1, the mass ratio of chitosan to titanium nitride powder is 5:1 to 400:1, the mass fraction of the ethanol suspension of copper-based nanoneedles is 0.01% to 10%, and the acid solution is acetic acid, hydrochloric acid, formic acid or oxalic acid.

[0019] Furthermore, the mass ratio of the aldehyde-modified polyaspartic acid to the hydrazide-modified hyaluronic acid is 1:10 to 1:2, and the thickness ratio of the hyaluronic acid hydrogel layer to the chitosan layer is 3:1 to 1:1.

[0020] A layered multifunctional antibacterial hydrogel dressing.

[0021] A layered multifunctional antibacterial hydrogel dressing is used in the treatment of infected skin wounds and local drug delivery of tumors and in the field of tissue engineering.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention adopts an in-situ oxidation method to form CuO2 on the surface of needle-shaped nano Cu(OH)2 to obtain copper-based nanoneedles, which can adjust the pH value, oxygen level and angiogenesis of the wound and promote wound healing. The copper-based nanoneedles are needle-shaped structures with copper hydroxide inside and copper peroxide on the surface. Under the action of wound exudate, they will decompose and release copper ions, oxygen, hydroxide and other substances. Copper ions will promote wound angiogenesis, oxygen will relieve wound hypoxia and facilitate cell growth and proliferation at the wound, and hydroxide will adjust the pH value at the wound, thereby promoting wound healing.

[0024] 2. In the preparation of the chitosan layer, copper-based nanoneedles and titanium nitride nanopowder are added, which effectively improves the strength and modulus of the chitosan layer. The chitosan layer in the present invention integrates the antibacterial properties of chitosan, copper-based nanoneedles and titanium nitride, namely the cationic antibacterial properties of chitosan, the antibacterial properties of copper ions and their Fenton-like reactions to generate hydroxyl radicals, and the photothermal antibacterial properties of titanium nitride, realizing the organic fusion of ionic antibacterial, chemical antibacterial and physical antibacterial, and having excellent comprehensive antibacterial properties. Compared with currently commonly used inorganic antibacterial agents such as nanogold, the antibacterial agent of the present invention has the advantages of low cost, simple and mild process, and scalable preparation.

[0025] 3. The chitosan layer in contact with the wound has low hydrophilicity and water absorption without deformation. The hyaluronic acid hydrogel layer has high water absorption and water retention capacity, and the layer interface is a porous structure, which ensures that the wound exudate can move quickly from the chitosan surface to the hyaluronic acid hydrogel layer through capillary action, thereby removing the wound exudate and coagulation factors such as coagulated platelets / proteins, preventing infection and promoting hemostasis.

[0026] 4. In the preparation of the hyaluronic acid hydrogel layer, aldehyde-modified polyaspartic acid was used as a cross-linking agent, which significantly improved the strength and dimensional stability of the hyaluronic acid hydrogel.

[0027] 5. The layered multifunctional hydrogel dressing of the present invention has outstanding one-way water pumping properties, and improves the interfacial bonding strength and structural stability of the layered hydrogel. At the interface of the two polysaccharide hydrogels, the copper-based nanoneedles in the chitosan layer can coordinate with the hydrazide hyaluronic acid in the hyaluronic acid hydrogel layer, and the aldehyde-modified polyaspartic acid in the hyaluronic acid hydrogel layer can react with the chitosan in the chitosan layer to produce a Schiff base reaction, and the two work together to significantly improve the interfacial bonding strength and structural stability. The layered hydrogel dressing of the present invention organically integrates the functions of one-way pump exudate removal, oxygen supply, antibacterial, hemostasis, and angiogenesis promotion, providing an innovative design solution for multifunctional antibacterial dressings, and has good application prospects in wound hemostasis and infectious wound treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a photo of the freeze-dried sample C prepared in Example 1; the white upper layer is the hyaluronic acid hydrogel layer, and the black lower layer is the chitosan layer;

[0029] Figure 2 is a transmission electron microscope photograph of the copper-based nanoneedles prepared in Example 1;

[0030] Figure 3 is the X-ray diffraction pattern of the copper-based nanoneedles prepared in Example 1;

[0031] Figure 4 1 is a scanning electron microscope photograph of sample C prepared in Example 1; wherein (a) is the hyaluronic acid hydrogel layer, (b) is the interface connection of the layered multifunctional gel dressing, and (c) is the chitosan layer.

[0032] Figure 5 The frequency scanning curves of Comparative Examples 1, 2 and Example 1;

[0033] Figure 6 are the strain scanning curves of Comparative Examples 1, 2 and Example 1;

[0034] Figure 7 is the shear thinning curve and injectable photograph of comparative example 1;

[0035] Figure 8 It is the injectable photo of comparative example 1;

[0036] Fig. 9 is the alternating strain curve of comparative example 1;

[0037] Fig.10 are the swelling curves of Comparative Example 1 and Example 1;

[0038] Fig.11 This is a physical picture of the water absorption and swelling of Example 1;

[0039] Fig.12 is the temperature rise curve of Example 1 under laser irradiation of different powers;

[0040] Fig.13 This is the photothermal cycle stability of Example 1 at 1W power.

[0041] Fig.14 It is the antibacterial results of Examples 1 to 3;

[0042] Fig.15 The biocompatibility results of Comparative Examples 1 and 2 and Examples 1 to 3 are as follows;

[0043] Fig.16 This is a diagram showing the effect of oxygen release of the copper-based nanoneedles prepared in Example 1 at different pH values ​​measured by a dissolved oxygen meter;

[0044] Fig.17 This is a graph using TMB as an indicator, with the absorbance at 650 nm representing the effect of the copper-based nanoneedles prepared in Example 1 releasing hydroxyl radicals at different addition amounts;

[0045] Fig.18 This is a diagram showing the effect of promoting cell migration in Example 1;

[0046] Fig.19 The hemostatic effect of Example 1 was tested by constructing a SD mouse liver bleeding model, wherein (a) is the control group and (b) is sample C. DETAILED DESCRIPTION

[0047] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.

[0048] Chitosan is a cationic polysaccharide, has excellent biocompatibility and biodegradability and good antibacterial, hemostatic and healing effects, and is a commonly used wound dressing raw material. However, chitosan is relatively low in hydrophilicity under neutral or weakly alkaline conditions, and does not deform after absorbing water, and has limited ability to absorb exudate and antibacterial, and can not give full play to its advantages in the case of a large amount of exudate in wounds. Hyaluronic acid is an anionic polysaccharide, is also one of the main components of the extracellular matrix, has excellent biocompatibility, biodegradability and water retention, and is widely used in hydrogel preparation. However, the strength of pure hyaluronic acid hydrogel is poor, and the deformation amount is large and the shape is unstable after absorbing water, and hyaluronic acid itself lacks functions such as antibacterial. So the present invention utilizes chitosan and hyaluronic acid to prepare antibacterial hydrogel dressing.

[0049] A layered multifunctional antibacterial hydrogel dressing of the present invention comprises a lower layer and an upper layer, wherein the lower layer is an antibacterial chitosan containing copper-based nanoneedles and titanium nitride nanopowders, and the upper layer is a hyaluronic acid cross-linked by aldehyde-modified polyaspartic acid with a water storage function, and this structure can unidirectionally transmit wound exudate from the chitosan layer to the hyaluronic acid hydrogel layer, thereby significantly improving the concentration of coagulation factors at the wound and accelerating hemostasis. The cationic properties of chitosan, the copper ions released by the copper-based nanoneedles and the hydroxyl radicals generated by hydrogen peroxide at the wound, the photothermal properties of titanium nitride, etc. give the chitosan lower layer excellent antibacterial properties, and the copper-based nanoneedles release oxygen at the same time, which can solve the problem of wound hypoxia, accelerate cell migration and wound healing. The hyaluronic acid hydrogel layer has a high water absorption capacity, and the wound exudate can be pumped out through the chitosan layer to maintain a moist environment and prevent bacterial infection. The hydrogel dressing has the advantages of good biocompatibility, strong water absorption capacity, excellent antibacterial properties, and broad application prospects in wound hemostasis, anti-infection and healing.

[0050] A method for preparing a layered multifunctional antibacterial hydrogel dressing of the present invention comprises the following steps:

[0051] The in-situ oxidation method was used to form CuO2 on the surface of needle-shaped nano-Cu(OH)2 to obtain copper-based nano-needles.

[0052] Titanium nitride nanopowder is uniformly dispersed in an acetic acid solution of chitosan under ultrasonic action, then injected into a mold and freeze-dried, washed alternately with alkali and alcohol, and then vacuum dried, and then soaked in an ethanol suspension of copper-based nanoneedles and then vacuum dried to obtain a non-swelling chitosan layer;

[0053] The aldehyde-modified polyaspartic acid aqueous solution and the hydrazide-modified hyaluronic acid aqueous solution are mixed evenly, placed in a mold to stand to form a swelling layer, and a chitosan layer is placed, and a layered multifunctional hydrogel dressing is obtained after freeze-drying. Among them, the swelling layer and the chitosan layer are connected by Schiff base bonds and copper-hydrazide coordination, showing the unidirectional transmission characteristics of the aqueous phase liquid from the chitosan layer to the hyaluronic acid hydrogel layer; the chitosan layer has cationic, copper ion and photothermal antibacterial functions, as well as hemostasis and hypoxia relief functions; the hyaluronic acid hydrogel layer has high water absorption and water retention capacity, and is used as a water storage layer.

[0054] Specifically, the preparation steps of copper-based nanoneedles are:

[0055] A copper salt (CuCl2 or Cu(NO3)2) aqueous solution with a concentration of 10-100mmol / L and a polyvinyl pyrrolidone aqueous solution with a concentration of 0.1%-10% (polyvinyl pyrrolidone is used as a dispersant, and the dispersant can also be CTAB or polyvinyl alcohol) are mixed in a volume ratio of 1:1-10:1, and then a NaOH solution with a concentration of 0.1-1mol / L is added dropwise, and after the addition is completed, it is stirred at 10000-13000rap / min for 5-30min to form needle-shaped nano Cu(OH)2, and then a H2O2 solution with a concentration of 0.1-1mol / L is added. After reacting for 0.1-6 hours, the copper-based nanoneedles are collected by centrifugation, and the length is 50-600nm and the diameter is 5-10nm. Among them, the molar ratio of copper salt to NaOH is 1:50-1:4, and the molar ratio of copper salt to H2O2 solution is 1:50-1:2.

[0056] Specifically, the chitosan layer is prepared by the following steps:

[0057] Chitosan is dissolved in an acetic acid (hydrochloric acid, formic acid or oxalic acid) solution with a mass concentration of 0.2% to 5% to obtain a solution with a chitosan mass fraction of 0.1% to 10%; then titanium nitride powder with a particle size of 10 to 300 nm is added, and the mass ratio of chitosan to titanium nitride powder is 5:1 to 400:1, and then injected into a mold after being evenly dispersed by ultrasound; after freeze drying for 1 to 3 days, the sample is alternately washed with a NaOH solution with a concentration of 0.1 to 1 mol / L and ethanol for 3 to 6 times and then vacuum dried; finally, the dried sample is immersed in a copper-based nanoneedle ethanol suspension with a mass concentration of 0.01% to 10% for 2 to 24 hours, and a chitosan layer is obtained after vacuum drying. Among them, the deacetylation degree of chitosan is ≥95%, and the viscosity is 100 to 200 mPa·s.

[0058] Specifically, the layered hydrogel dressing is prepared by the following process:

[0059] A aldehyde-modified polyaspartic acid (cross-linking agent) solution with a mass fraction of 0.025% to 30%, a aldehyde degree of 10% to 60%, and a molecular weight of 5kDa to 1000kDa is added dropwise to a hydrazide-modified hyaluronic acid aqueous solution with a mass fraction of 0.1% to 10%, a hydrazide degree of 10% to 40%, and a molecular weight of 10kDa to 3000kDa, the mass ratio of aldehyde-modified polyaspartic acid to hydrazide-modified hyaluronic acid being 1:10 to 1:2, mixed for 1 to 5 minutes, and then injected into a mold, followed by placing a chitosan layer, standing for 5 to 30 minutes, and then freeze-drying to form a layered hydrogel dressing. The layered hydrogel dressing includes a hyaluronic acid hydrogel layer and a chitosan layer with a thickness ratio of 1:1 to 3:1.

[0060] The layered multifunctional antibacterial hydrogel dressing prepared by the invention can be used in the fields of treating infected skin wounds, local administration of tumors, and tissue engineering, thereby reducing the risk of wound infection.

[0061] The following are specific embodiments.

[0062] Example 1

[0063] Preparation of copper-based nanoneedles: 40mmol / L CuCl2 aqueous solution and 1% polyvinyl pyrrolidone aqueous solution were mixed in a ratio of 1:1 to prepare a 10mL solution, and a 0.4mol / L NaOH solution was added dropwise. After the addition was completed, the mixture was stirred at 10000rap / min for 10min to form needle-shaped nano Cu(OH)2. Then 2mL of 0.5mol / L H2O2 solution was added. After reacting for 0.5 hours, the copper-based nanoneedles were collected by centrifugation. The molar ratio of CuCl2 to NaOH was 1:4.

[0064] The chitosan layer was prepared by the following steps:

[0065] 1g of chitosan was dissolved in an acetic acid solution with a mass concentration of 1% to obtain a solution with a chitosan mass fraction of 2%; then 5mg of titanium nitride powder with a particle size of 100nm was added, and the mixture was evenly dispersed by ultrasound and then injected into a mold; after freeze-drying for 1 day, the mixture was alternately washed with a 1mol / L NaOH solution and ethanol for 5 times and then vacuum dried; finally, the dried sample was immersed in a copper-based nanoneedle ethanol suspension with a mass concentration of 5% for 2 hours, and a chitosan layer was obtained after vacuum drying.

[0066] Prepare the layered hydrogel dressing:

[0067] 0.25 mL of aldehyde-modified polyaspartic acid solution with a mass fraction of 5%, a degree of aldehyde modification of 40%, and a molecular weight of 1000 kDa was added dropwise to 1 mL of hydrazide-modified hyaluronic acid aqueous solution with a mass fraction of 3%, a degree of hydrazide modification of 40%, and a molecular weight of 3000 kDa, mixed for 3 minutes, and then injected into a mold to form a hyaluronic acid hydrogel layer, followed by a chitosan layer, and then freeze-dried after standing for 10 minutes to obtain a layered hydrogel dressing, which was recorded as sample C. The thickness ratio of the hyaluronic acid hydrogel layer to the chitosan layer was 1:1.

[0068] See also Figure 2 , the average length of the copper-based nanoneedles is about 400 nanometers and the diameter is about 10 nanometers;

[0069] See also Figure 3 The X-ray diffraction pattern of copper-based nanoneedles shows that the main body of the nanoneedles is CuO2 and Cu(OH)2.

[0070] See also Figure 4 The scanning electron microscope image of sample C shows that the layered interface is clear and tightly connected, the pore structure of each layer is complete, and the pore size distribution is uniform.

[0071] See also Fig.11 After sample C absorbs water and swells, the chitosan layer can maintain a stable morphology, and the hyaluronic acid hydrogel layer can store a large amount of water.

[0072] See also Fig.12 , sample C has excellent photothermal performance

[0073] See also Fig.13 , sample C has excellent photothermal cycling stability.

[0074] See also Fig.16 The copper-based nanoneedles can slowly release oxygen at different pH values, and the speed and concentration of oxygen release are highest under acidic conditions, indicating that they have the potential to relieve wound hypoxia.

[0075] See also Fig.17 The higher the peak value, the more hydroxyl radicals are released. As the amount of copper-based nanoneedles added increases, the amount of hydroxyl radicals generated increases, indicating that it has the ability to release hydroxyl radicals to kill bacteria.

[0076] See also Fig.18 Compared with the control group, sample C could significantly promote cell migration.

[0077] See also Fig.19 In (a) and (b), sample C has excellent hemostatic function. Compared with the control group in Figure (a), the amount of bleeding in sample C in Figure (b) is significantly reduced.

[0078] Example 2

[0079] Preparation of copper-based nanoneedles: 40mmol / L CuCl2 aqueous solution and 1% polyvinyl pyrrolidone aqueous solution were mixed in a ratio of 1:1 to prepare a 10mL solution, 2mL of 0.4mol / L NaOH solution was added dropwise, and after the addition was completed, the mixture was stirred at 10000rap / min for 10min to form needle-shaped nano Cu(OH)2, and then 2mL of 0.5mol / L H2O2 solution was added. After reacting for 0.5 hours, the copper-based nanoneedles were collected by centrifugation. The molar ratio of CuCl2 to NaOH was 1:4.

[0080] The chitosan layer was prepared by the following steps:

[0081] 1g of chitosan was dissolved in an acetic acid solution with a mass concentration of 1% to obtain a solution with a chitosan mass fraction of 2%; then 5mg of titanium nitride powder with a particle size of 100nm was added, and the mixture was evenly dispersed by ultrasound and then injected into a mold; after freeze-drying for 1 day, the mixture was alternately washed with a 1mol / L NaOH solution and ethanol for 5 times and then vacuum dried; finally, the dried sample was immersed in a copper-based nanoneedle ethanol suspension with a mass concentration of 1% for 2 hours, and a chitosan layer was obtained after vacuum drying.

[0082] Prepare the layered hydrogel dressing:

[0083] 0.25 mL of aldehyde-modified polyaspartic acid solution with a mass fraction of 5%, a degree of aldehyde modification of 40%, and a molecular weight of 1000 kDa was added dropwise to 1 mL of hydrazide-modified hyaluronic acid aqueous solution with a mass fraction of 3%, a degree of hydrazide modification of 40%, and a molecular weight of 3000 kDa, mixed for 3 minutes, and then injected into a mold, followed by placing a chitosan layer, standing for 10 minutes, and freeze-drying to obtain a layered hydrogel dressing, which was recorded as sample D. The thickness ratio of the hyaluronic acid hydrogel layer to the chitosan layer was 1:1.

[0084] Example 3

[0085] Preparation of copper-based nanoneedles: 40mmol / L CuCl2 aqueous solution and 1% polyvinyl pyrrolidone aqueous solution were mixed in a ratio of 1:1 to prepare a 10mL solution, 2mL of 0.4mol / L NaOH solution was added dropwise, and after the addition was completed, the mixture was stirred at 10000rap / min for 10min to form needle-shaped nano Cu(OH)2, and then 2mL of 0.5mol / L H2O2 solution was added. After reacting for 0.5 hours, the copper-based nanoneedles were collected by centrifugation. The molar ratio of CuCl2 to NaOH was 1:4.

[0086] The chitosan layer was prepared by the following steps:

[0087] 1g of chitosan was dissolved in an acetic acid solution with a mass concentration of 1% to obtain a solution with a chitosan mass fraction of 2%; then 5mg of titanium nitride powder with a particle size of 100nm was added, and the mixture was evenly dispersed by ultrasound and then injected into a mold; after freeze-drying for 1 day, the mixture was alternately washed with a 1mol / L NaOH solution and ethanol for 5 times and then vacuum dried; finally, the dried sample was immersed in a copper-based nanoneedle ethanol suspension with a mass concentration of 5% for 2 hours, and a chitosan layer was obtained after vacuum drying.

[0088] Prepare the layered hydrogel dressing:

[0089] 0.25 mL of aldehyde-modified polyaspartic acid solution with a mass fraction of 5%, a degree of aldehyde modification of 40%, and a molecular weight of 1000 kDa was added dropwise to 1 mL of hydrazide-modified hyaluronic acid aqueous solution with a mass fraction of 3%, a degree of hydrazide modification of 40%, and a molecular weight of 3000 kDa, mixed for 3 minutes, and then injected into a mold, followed by placing a chitosan layer, standing for 10 minutes, and freeze-drying to obtain a layered hydrogel dressing, which was recorded as sample E. The thickness ratio of the hyaluronic acid hydrogel layer to the chitosan layer was 3:1.

[0090] See also Figure 5 ,Due to the high strength of titanium nitride and copper-based nanoneedle modified chitosan, the strength of sample B is higher than that of A and C. The strength of sample C is similar to that of sample A, indicating that after the double-layer composite, the strength of the sample is close to that of the single layer with lower strength.

[0091] See also Figure 6 , because the modified chitosan is not easy to deform, sample B is destroyed at a lower strain. Samples A and C have good toughness and can tolerate larger deformations, indicating that the double-layer composite sample has significantly improved toughness than the modified chitosan layer. , because the modified chitosan is not easy to deform, sample B is destroyed at a lower strain. Samples A and C have good toughness and can tolerate larger deformations, indicating that the double-layer composite sample has significantly improved toughness than the modified chitosan layer.

[0092] See also Fig.10 It can be seen that the swelling rate and equilibrium swelling ratio of sample C are significantly higher than those of sample B, indicating that sample C has excellent ability to absorb wound exudate. It can be seen that the water absorption rate and equilibrium swelling ratio of the double-layer composite gel are significantly greater than those of a single material.

[0093] See also Fig.14 ,It can be seen that the inhibition rate of different materials on Staphylococcus aureus and Escherichia coli was characterized by the colony counting method. Sample C has excellent antibacterial properties, and the bactericidal rate can reach more than 99%. The chitosan layer provides antibacterial properties in the layered gel dressing.

[0094] See also Fig.15By adding CCK-8 working solution and measuring the absorbance with a microplate reader to calculate the cell survival rate, the extract of sample C has good cell compatibility, and the cells proliferate normally as the culture time increases.

[0095] Example 4

[0096] Preparation of copper-based nanoneedles: A 10 mmol / L copper salt (CuCl2) aqueous solution and a 10% polyvinyl pyrrolidone aqueous solution were mixed in a volume ratio of 1:1 to prepare a 10 mL solution, and then a 0.6 mol / L NaOH solution was dropped into the solution. After the addition was completed, the solution was stirred at 10000 rap / min for 30 min to form needle-shaped nano Cu(OH)2. Then a 0.1 mol / L H2O2 solution was added dropwise. After reacting for 0.1 hour, the copper-based nanoneedles were collected by centrifugation, wherein the molar ratio of copper salt to NaOH was 1:4, and the molar ratio of copper salt to H2O2 solution was 1:30.

[0097] Preparation of chitosan layer:

[0098] Chitosan was dissolved in a hydrochloric acid solution with a mass concentration of 3% to obtain a solution with a mass fraction of chitosan of 5%; then titanium nitride powder with a particle size of 10 to 300 nm was added, and the mass ratio of chitosan to titanium nitride powder was 5:1, and then injected into a mold after being evenly dispersed by ultrasound; after freeze-drying for 2 days, the sample was alternately washed with a 0.5 mol / L NaOH solution and ethanol for 3 times and then vacuum dried; finally, the dried sample was immersed in a copper-based nanoneedle ethanol suspension with a mass concentration of 0.01% for 10 hours, and a chitosan layer was obtained after vacuum drying. Among them, the deacetylation degree of chitosan is ≥95%, and the viscosity is 100 to 200 mPa·s.

[0099] Preparation of layered hydrogel dressing: Add a 0.025% aldehyde polyaspartic acid (crosslinker) solution with a mass fraction of 30% and a molecular weight of 5kDa to a 6% hydrazide hyaluronic acid aqueous solution with a hydrazide degree of 250% and a molecular weight of 1000kDa, the mass ratio of aldehyde polyaspartic acid to hydrazide hyaluronic acid is 1:10, mix for 1 minute and inject into the mold, then place a chitosan layer, let it stand for 20 minutes and freeze-dry to form a layered hydrogel dressing. The layered hydrogel dressing includes a hyaluronic acid hydrogel layer and a chitosan layer with a thickness ratio of 2:1.

[0100] Example 5

[0101] Preparation of copper-based nanoneedles: A 100 mmol / L aqueous solution of copper salt (Cu(NO3)2) was mixed with a 4% aqueous solution of polyvinyl alcohol in a volume ratio of 10:1 to prepare a 10 mL solution, and then a 0.1 mol / L NaOH solution was added dropwise. After the addition was completed, the mixture was stirred at 13000 rap / min for 5 min to form needle-shaped nano Cu(OH)2. Then a 1 mol / L H2O2 solution was added. After 6 hours of reaction, the copper-based nanoneedles were collected by centrifugation, wherein the molar ratio of copper salt to NaOH was 1:20, and the molar ratio of copper salt to H2O2 solution was 1:2.

[0102] Preparation of chitosan layer:

[0103] Chitosan was dissolved in a hydrochloric acid solution with a mass concentration of 5% to obtain a solution with a mass fraction of chitosan of 0.1%; then titanium nitride powder with a particle size of 10 to 300 nm was added, and the mass ratio of chitosan to titanium nitride powder was 400:1, and then injected into a mold after being evenly dispersed by ultrasound; after freeze-drying for 3 days, the sample was alternately washed with a 1 mol / L NaOH solution and ethanol for 6 times and then vacuum dried; finally, the dried sample was immersed in a copper-based nanoneedle ethanol suspension with a mass concentration of 10% for 24 hours, and a chitosan layer was obtained after vacuum drying. Among them, the deacetylation degree of chitosan is ≥95%, and the viscosity is 100 to 200 mPa·s.

[0104] Preparation of layered hydrogel dressing: Add a 30% aldehyde polyaspartic acid (crosslinker) solution with a mass fraction of 10%, a aldehyde degree of 10%, and a molecular weight of 1000kDa to a hydrazide hyaluronic acid aqueous solution with a mass fraction of 0.1%, a hydrazide degree of 40%, and a molecular weight of 3000kDa, and the mass ratio of aldehyde polyaspartic acid to hydrazide hyaluronic acid is 1:2. After mixing for 5 minutes, inject into the mold, then place a chitosan layer, let it stand for 30 minutes, and then freeze-dry to form a layered hydrogel dressing. Among them, the layered hydrogel dressing includes a hyaluronic acid hydrogel layer and a chitosan layer with a thickness ratio of 3:1.

[0105] Example 6

[0106] Preparation of copper-based nanoneedles: A 50 mmol / L copper salt (CuCl2) aqueous solution and a 0.1% CTAB (hexadecyltrimethylammonium bromide) aqueous solution were mixed in a volume ratio of 5:1 to prepare a 10 mL solution, and then a 1 mol / L NaOH solution was added dropwise. After the addition was completed, the mixture was stirred at 12000 rap / min for 20 min to form needle-shaped nano Cu(OH)2. Then a 0.5 mol / L H2O2 solution was added. After reacting for 2 hours, the copper-based nanoneedles were collected by centrifugation, wherein the molar ratio of copper salt to NaOH was 1:50, and the molar ratio of copper salt to H2O2 solution was 1:50.

[0107] Preparation of chitosan layer:

[0108] Chitosan was dissolved in a hydrochloric acid solution with a mass concentration of 0.2% to obtain a solution with a chitosan mass fraction of 10%; then titanium nitride powder with a particle size of 10 to 300 nm was added, and the mass ratio of chitosan to titanium nitride powder was 100:1, and then injected into a mold after being evenly dispersed by ultrasound; after freeze-drying for 1 day, it was alternately washed with a 0.1 mol / L NaOH solution and ethanol for 5 times and then vacuum dried; finally, the dried sample was immersed in a copper-based nanoneedle ethanol suspension with a mass concentration of 4% for 2 hours, and a chitosan layer was obtained after vacuum drying. Among them, the deacetylation degree of chitosan is ≥95%, and the viscosity is 100 to 200 mPa·s.

[0109] Preparation of layered hydrogel dressing: A 10% mass fraction, 60% aldehyde degree, 400kDa molecular weight aldehyde polyaspartic acid (crosslinker) solution is added dropwise to a 10% mass fraction, 10% hydrazide degree, 10kDa molecular weight hydrazide hyaluronic acid aqueous solution, the mass ratio of aldehyde polyaspartic acid and hydrazide hyaluronic acid is 1:6, mixed for 3 minutes and then injected into a mold, followed by placing a chitosan layer, standing for 5 minutes and then freeze-drying to form a layered hydrogel dressing. Among them, the layered hydrogel dressing includes a hyaluronic acid hydrogel layer and a chitosan layer with a thickness ratio of 1:1.

[0110] Comparative Example 1

[0111] Add 5% aldehyde-modified polyaspartic acid dropwise to 3% hydrazide hyaluronic acid solution and mix for 3 minutes to form a uniform solution. The degree of aldehyde modification of polyaspartic acid is 40%, the molecular weight is 1000kDa, and the degree of hydrazide modification of hyaluronic acid is 40%, the molecular weight is 3000kDa. Inject the solution into a mold and let it stand for 5 to 30 minutes. The solution solidifies to form a hyaluronic acid water storage layer gel, which is recorded as sample A.

[0112] See also Figure 7 and Figure 8 , Sample A has good shear thinning properties, indicating that Sample A has injectable properties, can be smoothly extruded from a syringe, and can fill irregularly shaped wounds by injection.

[0113] See also Figure 8 , Sample A has excellent self-healing properties and can quickly recover to its state before being damaged under alternating strain, indicating that Sample A can adapt to wounds of different shapes and sizes and is convenient for practical application. The surface sample can quickly recover to its initial state after being damaged by external force, has self-healing ability, and can adapt to wounds of different shapes and sizes.

[0114] Comparative Example 2

[0115] Preparation of copper-based nanoneedles: A 40 mmol / L CuCl2 aqueous solution and a 1% polyvinyl pyrrolidone aqueous solution were mixed in a 1:1 ratio, and a 0.4 mol / L NaOH solution and a H2O2 solution were added dropwise in sequence. After reacting for 0.5 hours, the copper-based nanoneedles were collected by centrifugation. The molar ratio of CuCl2 to NaOH was 1:4.

[0116] The chitosan layer was prepared by the following steps:

[0117] Chitosan was dissolved in 1% acetic acid solution to obtain a solution with a chitosan mass fraction of 2%; then titanium nitride powder with a particle size of 100 nm was added, and the mixture was evenly dispersed by ultrasound and then injected into a mold; after freeze-drying for 1 day, the mixture was alternately washed with 1 mol / L NaOH solution and ethanol for 5 times and then vacuum dried; finally, the dried sample was immersed in a copper-based nanoneedle ethanol suspension with a mass concentration of 5% for 2 hours, and sample B was obtained after vacuum drying.

[0118] Comparative Example 1 is a hyaluronic acid hydrogel layer (single layer), and Comparative Example 2 is a chitosan layer (single layer). The mechanical properties are compared with the layered gel dressing of the present invention to illustrate the role of each layer.

[0119] See also Figure 5 ,It can be seen that the layered gel dressing has higher strength and cross-linking degree than the single hyaluronic acid hydrogel layer because the chitosan layer provides support and interlayer cross-linking.

[0120] See also Figure 6 It can be seen that the layered gel dressing has much higher toughness than the single chitosan layer because the hyaluronic acid hydrogel layer bears the deformation and interlayer cross-linking effect, and can withstand large external deformation.

[0121] The layered gel dressing prepared by the present invention combines the mechanical property advantages of two single layers (the hyaluronic acid hydrogel layer and the chitosan layer) and has better strength and toughness.

[0122] The part of the layered gel dressing prepared by the present invention that provides injectability and self-healing properties is the hyaluronic acid hydrogel layer.

[0123] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.

[0124] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

Claims

1. A method for preparing a layered multifunctional antibacterial hydrogel dressing, characterized in that: The following steps are involved: The in-situ oxidation method was used to form CuO2 on the surface of needle-shaped nano-Cu(OH)2 to obtain copper-based nano-needles. The titanium nitride nanopowder is uniformly dispersed in an acetic acid solution of chitosan, freeze-dried, and then soaked in an ethanol suspension of copper-based nanoneedles and vacuum-dried to obtain a chitosan layer; The aldehyde-modified polyaspartic acid aqueous solution and the hydrazide-modified hyaluronic acid aqueous solution are mixed evenly, and allowed to stand to form a hyaluronic acid hydrogel layer. A chitosan layer is placed on the hyaluronic acid hydrogel layer, and freeze-dried to obtain a layered multifunctional hydrogel dressing.

2. The method for preparing the layered multifunctional antibacterial hydrogel dressing according to claim 1, characterized in that: The length of the copper-based nanoneedles is 50 to 600 nm and the diameter is 5 to 10 nm.

3. The method for preparing the layered multifunctional antibacterial hydrogel dressing according to claim 1, characterized in that: The preparation steps of copper-based nanoneedles are: The copper salt aqueous solution is mixed with the dispersant aqueous solution, and then the NaOH solution is added and stirred to form needle-shaped nano Cu(OH)2, and then the H2O2 solution is added to react to obtain copper-based nano needles.

4. The method for preparing the layered multifunctional antibacterial hydrogel dressing according to claim 3, characterized in that: The copper salt is CuCl2 or Cu(NO3)2, and the dispersant is polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide or polyvinyl alcohol.

5. The method for preparing the layered multifunctional antibacterial hydrogel dressing according to claim 3, characterized in that: The concentration of the copper salt aqueous solution is 10-100 mmol / L, the mass concentration of the dispersant aqueous solution is 0.1%-10%, the volume ratio of the copper salt aqueous solution to the dispersant aqueous solution is 1:1-10:1, the molar ratio of the copper salt to NaOH is 1:50-1:4, the concentration of the H2O2 solution is 0.1-1 mol / L, and the molar ratio of the copper salt to the H2O2 solution is 1:50-1:

2.

6. The method for preparing the layered multifunctional antibacterial hydrogel dressing according to claim 1, characterized in that: The chitosan layer was prepared by the following steps: Chitosan is dissolved in an acid solution, and then titanium nitride powder is added, and after being evenly dispersed by ultrasonication and freeze-dried, the solution is immersed in a copper-based nanoneedle ethanol suspension, and vacuum dried to obtain a chitosan layer.

7. The method for preparing the layered multifunctional antibacterial hydrogel dressing according to claim 6, characterized in that: The particle size of the titanium nitride powder is 10 to 300 nm, the deacetylation degree of chitosan is ≥95%, and the viscosity is 100 to 200 mPa·s; the mass ratio of chitosan to acetic acid is 2:1 to 50:1, the mass ratio of chitosan to titanium nitride powder is 5:1 to 400:1, the mass fraction of the ethanol suspension of the copper-based nanoneedles is 0.01% to 10%, and the acid solution is acetic acid, hydrochloric acid, formic acid or oxalic acid.

8. The method for preparing the layered multifunctional antibacterial hydrogel dressing according to claim 6, characterized in that: The mass ratio of aldehyde-modified polyaspartic acid to hydrazide-modified hyaluronic acid is 1:10-1:2, and the thickness ratio of the hyaluronic acid hydrogel layer to the chitosan layer is 3:1-1:

1.

9. A layered multifunctional antibacterial hydrogel dressing prepared according to the method according to any one of claims 1 to 8.

10. Use of the layered multifunctional antibacterial hydrogel dressing prepared according to the method of any one of claims 1 to 8 in the treatment of infected skin wounds and local administration of tumors and in the field of tissue engineering.

Citation Information

Patent Citations

  • Copper ion antibacterial hydrogel as well as preparation method and application thereof

    CN112480434A

  • Hyaluronic acid / polyaspartic acid interconnection network hydrogel loaded with iron-based nano-enzyme as well as preparation method and application of hyaluronic acid / polyaspartic acid interconnection network hydrogel

    CN118436846A

  • Method for reducing post-operative scar formation using materials comprising copper, zinc and / or silver compounds applied under peripheral pressure

    WO2022091102A1